1993
DOI: 10.1161/01.cir.88.5.2172
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and coronary heart disease risk factor trends. The Minnesota Heart Survey.

Abstract: Improvement in CHD risk factors over time unrelated to education or income suggests that population-wide factors such as improved health knowledge, availability of healthy food items, hypertension treatment, and restrictions on cigarette smoking are operating beneficially in all SES groups. Although the SES gradient in risk factors is not increasing, it remains substantial and indicates directions for future prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
88
3
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(112 citation statements)
references
References 30 publications
12
88
3
9
Order By: Relevance
“…This is consistent with previous studies (16 -20) that reported more pronounced inverse associations between educational level and features of metabolic syndrome in women than in men. The reasons for this association might be related to the influence of education in predicting food choices (22,30 -33) and healthy behaviors (30,34), both of which are related to metabolic syndrome. Since education facilitates the understanding and acquisition of healthy lifestyles and since women are generally more health conscious than men, the combination of both factors might explain the greater protection against metabolic syndrome in educated women.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This is consistent with previous studies (16 -20) that reported more pronounced inverse associations between educational level and features of metabolic syndrome in women than in men. The reasons for this association might be related to the influence of education in predicting food choices (22,30 -33) and healthy behaviors (30,34), both of which are related to metabolic syndrome. Since education facilitates the understanding and acquisition of healthy lifestyles and since women are generally more health conscious than men, the combination of both factors might explain the greater protection against metabolic syndrome in educated women.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, after the middle of the 20th century this changed gradually, especially in Westernized countries, so that CVD is currently more common in lower socio-economic groups (6)(7)(8)(9) . Moreover, nowadays observational studies show that low SES individuals are associated with increased prevalence of CVD risk factors, such as hypertension, sedentary life, unhealthy dietary habits, cigarette smoking and high cholesterol (10)(11)(12)(13) . It has been hypothesized that dietary choices may be one of the many factors mediating the relationship between social class and CVD risk.…”
mentioning
confidence: 99%
“…Previous studies such as the Minnesota Heart Survey and the ATTICA study have demonstrated that low socioeconomic status can increase CAD risk factors or can predict unhealthy risk patterns (23,24) . Along the same lines, our results show that the control group reported higher education levels and higher financial status when compared with CAD patients.…”
Section: Discussionmentioning
confidence: 99%